2012
DOI: 10.1042/bsr20120067
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular conversion of adiponectin hexamers into trimers

Abstract: Adiponectin is an adipocyte-secreted hormone that exists as trimers, hexamers and larger species collectively referred to as HMW (high-molecular-weight) adiponectin. Whether hexamers or HMW adiponectin serve as precursors for trimers outside the circulation is currently unknown. Here, we demonstrate that adiponectin trimers can be generated from larger oligomers secreted from primary rat adipose cells or differentiated 3T3-L1 adipocytes. Purified hexameric, but not HMW, adiponectin converted into trimers in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 52 publications
(88 reference statements)
1
8
0
Order By: Relevance
“…Previous studies (25,47) have reported that fully oxidized LMW adiponectin and MMW adiponectin fail to assemble into the HMW form, whereas reduced trimers could assemble into the HMW form through oxidative formation of disulfide bonds in vitro and in vivo (25,47,50). These observations indicate that the MMW form comprises oxidized trimers that are assembly-trapped.…”
Section: Erp44 Binding Depends On the Relative Location Of The Cys 39supporting
confidence: 46%
“…Previous studies (25,47) have reported that fully oxidized LMW adiponectin and MMW adiponectin fail to assemble into the HMW form, whereas reduced trimers could assemble into the HMW form through oxidative formation of disulfide bonds in vitro and in vivo (25,47,50). These observations indicate that the MMW form comprises oxidized trimers that are assembly-trapped.…”
Section: Erp44 Binding Depends On the Relative Location Of The Cys 39supporting
confidence: 46%
“…Mature monomeric adiponectin has a molecular weight of *26 kDa [9]. As human adiponectin circulates in plasma/ serum mainly as trimers (LMW, *78 kDa), hexamers (MMW, *156 kDa) and 12-18-mers (HMW, [300 kDa) isoforms [7], hTrx1 binding to different adiponectin isoforms was thus analyzed.…”
Section: Htrx1-adiponectin Complexmentioning
confidence: 99%
“…Adiponectin isoforms have differential actions [8]. Mature monomeric adiponectin has a molecular weight about 26 kDa [9]. The HMW and MMW isoforms of adiponectin are composed of disulfide bonded trimer [10].…”
Section: Introductionmentioning
confidence: 99%
“…20 Adiponectin exists as trimers, hexamers, and as higher molecular weight forms in the circulation. 28 Because of extremely high circulating levels of the hormone, some have proposed that altering the ratio of circulating adiponectin to higher molecular weight forms would be a more advantageous therapeutic approach than increasing its total levels. The disulfide bond A oxidoreductase-like protein promotes adiponectin multimerization, and overexpression of disulfide bond A oxidoreductase-like protein in mice shows beneficial effects on insulin resistance.…”
Section: Circulation Researchmentioning
confidence: 99%
“…Methods to enhance proteolytic cleavage of full length adiponectin to gAd may serve as a potential therapeutic approach for enhancing adiponectin bioactivity. 28 Additional research on the role of adiponectin as a therapeutic agent may lead to the development of an additional safe intervention to help curtail the epidemic of metabolic and cardiovascular diseases.…”
Section: Circulation Researchmentioning
confidence: 99%